IMPROVING THE ACCOUNTING OF INTANGIBLE ASSETS IN JOINT VENTURES BASED ON INTERNATIONAL STANDARDS: https://doi.org/10.5281/zenodo.15390676 - Yusupov , Asror (Journal of Contemporary World Studies, 2025)
Intangible assets are a vital component of the balance sheets of joint ventures (JVs), particularly in sectors such as technology, pharmaceuticals, and intellectual property-driven businesses. The accounting of intangible assets, however, remains complex and varied, especially in joint ventures where ownership and control are shared. This article explores the challenges and opportunities in improving the accounting of intangible assets in joint ventures in accordance with international accounting standards. By focusing on the relevant provisions of IFRS (International Financial Reporting Standards), particularly IAS 38, the study examines how joint ventures can enhance transparency, consistency, and accuracy in the recognition, measurement, and reporting of intangible assets. The paper also reviews best practices, identifies key challenges, and proposes recommendations for improving the accounting practices surrounding intangible assets in JVs.